Alkaloid Extract of Equisetum arvense Plant Induce Apoptosis in MCF7 Cancer Cell Line - Abeer H. Ahmed; Amer T. Tawfeeq; Ibrahim H. Mohammed (Iraqi Journal of Cancer and Medical Genetics, 2020)
This study was conducted to detect the ability of an alkaloid extracted from Equisetum arvense to induce apoptosis on MCF7 cancer cells. The IC50 concentration was employed in these experiments (325 μg/ml at 24hr), it was obtained from studying the effect of the alkaloid extract on the growth inhibition of cancer cells after 24 hours of exposure. genes involved in apoptosis (P53, BAX, Caspase8, and Caspase9) were assessed on the mRNA level.besides that, a study for the cells morphological changes that occurred via apoptosis was carried out by staining with a mixture of two fluorescence dyes acridine orange and propidium iodide. Mitochondrial membrane potential was also assessed. The results showed that the expression level of apoptosis genes was elevated. Apoptosis like morphological changes was noticed in cellular membranes and nucleus. Apoptosis characterization of the mitochondria membrane was detected as well. These results revealed the capability of this alkaloid extract to induce apoptosis in this breast cancer cell line. This study confirmed the substantial cytotoxic and pro-apoptotic activity of Equisetum arvense alkaloid extract toward the studied cell line, which indicates the utility of this substance in anticancer therapy.